2011
DOI: 10.1002/bies.201100015
|View full text |Cite
|
Sign up to set email alerts
|

β‐Cell evolution: How the pancreas borrowed from the brain

Abstract: Editor's suggested further reading in BioEssaysA new paradigm in cell therapy for diabetes: Turning pancreatic α‐cells into β‐cells Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 74 publications
3
35
0
Order By: Relevance
“…PP cells have substantial expression of genes related to neuronal cells, which hints at the developmental proximity of PP and neuronal cells. This has been previously described by others in the context of beta cells (Arntfield and van der Kooy, 2011, Le Roith et al., 1982)…”
Section: Resultssupporting
confidence: 74%
“…PP cells have substantial expression of genes related to neuronal cells, which hints at the developmental proximity of PP and neuronal cells. This has been previously described by others in the context of beta cells (Arntfield and van der Kooy, 2011, Le Roith et al., 1982)…”
Section: Resultssupporting
confidence: 74%
“…Phylogenetic analyses of insulin-producing cells suggest that mammalian β-cells and fly IPCs have common evolutionary origins or have different origins but have undergone convergent evolution (Arntfield and Van Der Kooy 2011). Mammalian β-cells arise from the endoderm (Jensen 2004), and fly IPCs are neurons arising from the ectoderm (Wang et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Fly IPCs have long axons requiring extensive transport of vesicles, while β-cells have no axons. Yet phylogenic analyses of insulin-expressing cells indicate that neurons evolved to secrete insulin before there were β-cells, creating a puzzle about the evolutionary origin of β-cells (Arntfield and Van Der Kooy 2011). In jellyfish, insulin is produced only by neurons (Davidson et al 1971).…”
Section: Discussionmentioning
confidence: 99%
“…This is due, in part, to an evolving realization that beta-cells and neurons possess striking similarities, both functionally and in genetic profile. In 2011 Arntfield and van der Kooy summarized the similarities between neurons and beta-cells and suggested that in an instance of convergent evolution, beta-cells are “borrowed from the brain” (Table 1, [2244]). Basically, neurons and beta-cells are derived from different tissue layers, ectoderm and endoderm respectively, but are very similar in the way that they store, respond to, and transmit signaling molecules.…”
Section: Borrowed Evolution: Beta-cells and Neuronsmentioning
confidence: 99%